The Role of Institutional Repositories in Promoting Grey Literature in Academic Libraries in Tanzania - Samzugi, Athuman (University of Dar es Salaam Library Journal, 2018)
This paper is based on a study, which examined the role of Institutional Repositories (IRs) in promoting Grey Literature in Tanzania ' s academic libraries. Specifically, the study assessed the status and date birth of IRs in academic libraries in Tanzania; examined the types of content covered in the institutional repositories of academic libraries in Tanzania; and determined the policies on management of IRs in academic libraries in Tanzania. Purposive sampling was used to select population for the study. Data for the study was collected using a combination of methods including Institutional Repositories web-based survey conducted from September to November, 2016 and telephone interviews with five (5) directors of academic libraries to enhance the validity and reliability of data collected because each method has its strengths and weaknesses. Content analysis was conducted by visiting individual IRs. To accommodate the research problem and fulfil the objectives of the study, 31 public and private universities registered on the website of the Tanzania Commission for Universities (TCU) participated in the study. The data obtained from the TCU were verified through the directory of the Open Access Repository (OpenDOAR) because it is the authoritative directory of Open Access Repositories in the world. Key findings indicate that, the uptake of institutional repositories in academic libraries in Tanzania was in their formative stages and are not full-fledged as most of them started the implementation in 2012-2016.Out of the 31 academic libraries only eight (8) had an IRs in place. Findings further revealed that content types available in the IRs showed the majority (7,533[60.2%]) was grey literature. The study concluded that, many academic libraries in Tanzania have great potential of putting in place IRs that can increase the collection, preservation and visibility of research outputs in the form of grey literature, but have yet to do so. As such, the study recommends that, first, through internally-generated funds such as tuition fees and in collaboration with other stakeholders including the government, the university managements should support the establishment and sustainability of IRs in their respective institutions. Second, the Consortium of Tanzania Universities and Research Libraries (COTUL) should raise awareness amongst managements of universities and the Tanzania Commission for Universities (TCU), academic staff and students on the centrality of institutional repositories in the collection, storage and dissemination of digitally-borne intellectual output they generate such as grey literature. Third, since academic libraries have started to embrace IRs, they should also develop clear and explicit policies for supporting the development, management and operational procedures for management of digital information resources in the IRs.